Faith and South African realities in practising forgiveness - Denton, Rudy Arthur (HTS teologiese studies, 2018)
The invocation and necessity of a forgiveness process have become complicated and multifaceted within the South African society with its realities of crime, poverty, racism, injustice and abuse. The rhythms of forgiveness compel us to identify our present situation. Individuals, as well as larger social groups, should begin to reflect on the importance of forgiveness to deal with transgression, violence, revenge and bitterness. I suggest that forgiveness within the Christian doctrine needs to be situated and embodied in specific habits and practices of Christian life within the South African society. In response, people in South Africa are called to remember past transgressions while pursuing the repairing and healing of the brokenness and separations in relationships by embodying forgiveness. It directs the importance of the Church’s prophetic task to proclaim the boundless gift of a constructive and transformative relationship with God, one another and God’s creation. Practising forgiveness includes a process of seeking to embody Christian forgiveness that involves the transformation of people’s lives, their world and their capability to restore communion within the field of social relations.